2010
DOI: 10.1093/schbul/sbq124
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Smoking Risks and Motivation to Quit Among Nontreatment-Seeking Smokers With and Without Schizophrenia

Abstract: This study underscores the degree to which people with schizophrenia perceive the state-enhancing effects of smoking and their lower appreciation for health risks of smoking compared with normal controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 40 publications
3
45
0
5
Order By: Relevance
“…Other potential reasons include self-medication of negative/cognitive symptoms and neurophysiological abnormalities (Winterer 2010), depressive symptoms (Lising-Enruquez and George 2009), a means of activity or staving off boredom (Roick et al 2007), or to decrease the extrapyramidal side effects of antipsychotics (Madden et al 1997). Previous work from our group has found that people with schizophrenia report more frequently than controls that smoking improves the ease of social interaction and state enhancement (Kelly et al 2010). However, a recent study (Levander et al 2007) found no difference between nicotine users and non-users with schizophrenia spectrum disorders on symptoms, side effect, cognition, and outcome.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Other potential reasons include self-medication of negative/cognitive symptoms and neurophysiological abnormalities (Winterer 2010), depressive symptoms (Lising-Enruquez and George 2009), a means of activity or staving off boredom (Roick et al 2007), or to decrease the extrapyramidal side effects of antipsychotics (Madden et al 1997). Previous work from our group has found that people with schizophrenia report more frequently than controls that smoking improves the ease of social interaction and state enhancement (Kelly et al 2010). However, a recent study (Levander et al 2007) found no difference between nicotine users and non-users with schizophrenia spectrum disorders on symptoms, side effect, cognition, and outcome.…”
Section: Introductionmentioning
confidence: 89%
“…Studies of cessation interventions in patients with schizophrenia have found varying rates of success, although positive results have been reported in the literature (Baker et al 2006; George et al 2008). Motivation for quitting may be lower in schizophrenia, as Kelly et al (2010) found that motivation for quitting smoking in persons with schizophrenia is significantly lower than in controls. Baker et al (2007) reported that, compared to general population samples, persons with psychotic disorders were more likely to indicate that stress reduction, stimulation, and addiction were reasons for smoking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are more motivated to receive support once they have decided to quit [82]. Patients with schizophrenia are less motivated to quit compared to general smokers [87,88]. Most of them think that smoking helps to alleviate negative symptoms and cognitive deficits, enhances cognitive performance, and provides psychomotor stimulation [17,89].…”
Section: Awareness and Motivation Patients With Chd Whomentioning
confidence: 99%
“…Participants completed assessments gathering demographics, smoking history/behavior, and nicotine dependence. This study is a secondary analysis of a larger study examining smoking craving between smokers with schizophrenia and healthy smokers (Kelly et al, 2012; Lo et al, 2011; Mackowick et al, 2012). This analysis will report the smoking characteristics of smokers with schizophrenia by antipsychotic group.…”
Section: Methodsmentioning
confidence: 99%